(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
We propose the Jacobi spectral Galerkin and Jacobi spectral multi Galerkin methods with their iterated versions for obtaining the superconvergence results of a general class of nonlinear Volterra integral equations with a kernel x^β(z-x)^-κ, where 0